Necesidad de regular en el art. 59 de la ley de minería un mecanismo para la fiscalización de la producción minera - Jaramillo Vélez, José Manuel (2014)
The Art. 16 of the Mining Act provides the authority to control, an issue that must be properly regulated by the same law to verify the actual volumes being extracted, the exploitation same meaning scale, because the material is taken raw stages of processing material removed. If the mechanism of control of the production is made, leading to large mining companies that exploit and carried crude production, without thereby weighed a fact exploited the specific amount of material and the different types of minerals which are therefore tax evasion brings detriment of the Treasury, and the royalties they owe the state and thus the community would not be the real benefit for the deterioration of the environment, and as a kind of compensation for being accented peoples in the concessions granted by the state to transnational, exploiting mineral scale and open pit. Verify quantities that are exploited, to manage, regulate and control strategic sectors as indicated in Art. 313 of the Constitution of the Republic of Ecuador, and therefore in the State management should prioritize intergenerational responsibility, the collection of royalties and other non-tax contributions as expressed in Art. 317 of the Constitution. Being important the control of the production the Central Government has entered into mineral exploitation on a large scale, for example be mined copper concentrate, ie will be raw material and the Agency for the Regulation and Control of Mining, no has the experience and mechanisms to control this. The Mining Law establishes the production report, the granting of abandoned waste, Authorization for installation and operation of plants, semi-annual, rights and obligations, right of free marketing, marketing license, obligations of traders, cancellation of license clandestine trade in minerals, illegal exploitation of mining, illegal sanctions on mining activity, but does not provide a mechanism to control production, exploration and exploitation of resources, which there is not a strategy for environmental sustainability.